INVESTIGATING THE CHALLENGES OF DIGITAL COMPETENCE AMONG ENGLISH TEACHERS IN METRO LAMPUNG JUNIOR HIGH SCHOOLS - Umi Yawisah; Yeasy Agustina Sari; Suhono Suhono; Raga Driyan Pratama; Andi Mappewali (Nurul Jadid University, 2026)
This study aims to investigate the problem of Digital Competence 2.2 of English instructors of Metro Lampung junior high school. This qualitative study used semi-structured interviews with 20 English teachers from public and private junior high schools in urban, semi-urban and rural areas. Participants were purposefully sampled to represent a variety of teaching scenarios. The five DigComp 2.2 competence areas: Information & Data Literacy, Communication & Collaboration, Digital Content Creation, Safety, and Problem were used to analyze data using theme analysis. Solving- Triangulation, member checking, and peer debriefing were used to establish trustworthiness. The results suggest teachers confront different barriers in the DigComp areas. Teachers are challenged in information and data literacy with search methods, information verification, and digital file management. Basic messaging apps are used more for communication and cooperation than pedagogically rich collaborative systems. The biggest issues teachers have included lack of confidence in designing digital materials, understanding copyright rules, and adapting multimedia resources. Teachers are less aware of data security, cyber hygiene, and digital well-being.